Genetic Code Engineering by Natural and Unnatural Base Pair Systems for the Site-Specific Incorporation of Non-Standard Amino Acids Into Proteins - Kimoto, Michiko; Hirao, Ichiro (Frontiers in Molecular Biosciences, 2022)
Amino acid sequences of proteins are encoded in nucleic acids composed of four letters, A, G, C, and T(U). However, this four-letter alphabet coding system limits further functionalities of proteins by the twenty letters of amino acids. If we expand the genetic code or develop alternative codes, we could create novel biological systems and biotechnologies by the site-specific incorporation of non-standard amino acids (or unnatural amino acids, unAAs) into proteins. To this end, new codons and their complementary anticodons are required for unAAs. In this review, we introduce the current status of methods to incorporate new amino acids into proteins by in vitro and in vivo translation systems, by focusing on the creation of new codon-anticodon interactions, including unnatural base pair systems for genetic alphabet expansion.